Design and Analysis of Floater Structures using Composite Material in 19 Seaters Aircraft - Andi Muhdiar Kadir; Arief Setyawan; Fithri Nur Purnamasari; Nurhadi Pramana; Muhammad; Ilham Akbar Adi Satriya; Riza Wirawan; Budi Sampurno (International Journal of Technology)
One of the government's programs for connecting cities and remote Indonesian islands were quickly utilized by amphibious aircraft. This was realized with the amphibious N219 program started in 2018. The N219, referred to for Nusantara, its twin engines, and 19-passenger capacity, represents Indonesia's ambition to link its extensive archipelago through innovation and pride. The N219 amphibious aircraft was developed based on the N219 basic aircraft (maximum take-off weight, MTOW 7030 kg), with the incorporation of two floats, enabling it to land on both land and water surfaces. It was intended that the addition of this float would not significantly change the performance of the N219 aircraft, so there was no need to make big changes in terms of the number of passengers. one of the important factors in this performance was the weight penalty. In this research, structural analysis was done to reduce the weight of floaters by applying the optimal design dan used the sandwich composite materials. The specimens of carbon composite were produced by Vacuum-Assisted Resin Infusion/ VARI. The specimens with five fiber orientation variations (UD: 0o, 90o, and 45o and Fabric: ±45o and 0o/90o) were tested, and the results were utilized as data input for finite element analysis. Floater structure modeling was conducted to predict its strength and weight. The modeling analysis results showed that the maximum stress was 354.2 MPa < 1014 MPa (material test result). Meanwhile, the Tsai-wu criteria were 0.550, where it's <1, and the mass of the floater found was 274 kg, where it's <400 kg. It could be seen that the floater structure design using carbon composite materials had good results, so it could be considered for implementation.